Mechanical Allodynia Predicts Better Outcome of Surgical Decompression for Painful Diabetic Peripheral Neuropathy - Liao, Chenlong; Nickerson, D. Scott; Visocchi, Massimiliano; Yang, Min; Liu, Pengfei; Zhong, Wenxiang; Zhou, Han; Zhang, Wenchuan (Journal of Reconstructive Microsurgery, 2018)
Background To determine the role of mechanical allodynia (MA) in predicting good surgical outcome for painful diabetic peripheral neuropathy (DPN).Materials and Methods Data of 192 patients with painful DPN were collected in this study, with 148 surgical patients and 44 patients in the control group. Both groups were further divided into subgroups based on the presence of MA on admission. Clinical evaluations including the visual analog scale (VAS), the Hospital Anxiety and Depression Scale (HADS), nerve conduction velocity (NCV), and high-resolution ultrasonography (cross-sectional area, CSA) were performed preoperatively and postoperatively.Results The levels of VAS and HADS and the results of NCV and CSA were improved in the surgical group (p < 0.05). In the surgical subgroups, pain reduction, psychiatric amelioration, improvement in NCVs, and the restoration of the CSA were observed in patients with signs of MA (p < 0.05), whereas only pain reduction, psychiatric amelioration, and restoration of the CSA were noted in patients without signs of MA (p > 0.05). Furthermore, better pain reduction was achieved in patients with MA when compared with those without MA (p < 0.05).Conclusions MA is proved to be a reliable predictor of good surgical outcome for painful DPN.
Keywords: diabetic peripheral neuropathy; mechanical allodynia; nerve decompression